Pengaruh Lama Penyimpanan Hasil Fermentasi Pelepah Sawit Oleh Trichoderma Sp Terhadap Kandungan Selulosa Dan Hemiselulosa - Achmad Jaelani; Siti Dharmawati; Bayu Lesmana (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
The research aims to determine the effect of storage time of palm fronds fermented by trichoderma sp to cellulose and hemicellulose content. The method in the research by the using a Completely Randomized Design (CRD) which consists of 5 treatments and 4 replications. Treatment using Trichoderma sp by 6% in the ratio 2:1 with the storage time P0 (0 weeks), P3 (3 weeks), P6 (6 weeks), P9 (9 weeks), and P12 (12 weeks). The variable were observed in this research that the level of cellulose and hemicellulose in palm fronds, with the support of the supporting variables such as odor, color, and texture of fermented palm fronds with a different storage time. Data were the using analysis of variance and to know the difference between treatment followed by DMRT (Gaspersz, 1994). The result showed that were significant differences between the storage time of fermented plam fronds against cellulose content, the highest cellulose content in P12 week storage time is 53,83%. For the hemicellulose content of fermented palm fronds with a differrent storage time, the content of hemicellulose to decrease and no real effect. Decrease in hemicellulose content lowest for the storage P9 week time is 20,19%.